2013
DOI: 10.1590/s0100-83582013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seed size and ecological factors on the germination and emergence of field bindweed (Convolvulus arvensis)

Abstract: -An understanding of seed germination ecology of weeds can assist in predicting their potential distribution and developing effective management strategies. Influence of environmental factors and seed size on germination and seedling emergence of Convolvulus arvensis (field bindweed) was studied in laboratory and greenhouse conditions. Germination occurred over a wide range of constant temperatures, between 15 and 40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
2
29
0
2
Order By: Relevance
“…As in the case of rosette leaf number, the correlation was not significant in our small sample size (P < 0.35). Nevertheless, the trend was consistent with previous studies that showed intraspecific selection for rapid germination can lead to an increase in seed size and evolution of invasiveness (Graebner et al 2012;Tanveer et al 2013;Torices et al 2013). Given that ecological studies on germination speed have suggested a strong relationship with seed size and competitiveness (Dubois & Cheptou 2012;Lonnberg & Eriksson 2013;Afonso et al 2014;Leverett & Jolls 2014), our finding may suggest that the competitiveness of larger seeds is partly mediated by rapid germination.…”
Section: Discussionsupporting
confidence: 92%
“…As in the case of rosette leaf number, the correlation was not significant in our small sample size (P < 0.35). Nevertheless, the trend was consistent with previous studies that showed intraspecific selection for rapid germination can lead to an increase in seed size and evolution of invasiveness (Graebner et al 2012;Tanveer et al 2013;Torices et al 2013). Given that ecological studies on germination speed have suggested a strong relationship with seed size and competitiveness (Dubois & Cheptou 2012;Lonnberg & Eriksson 2013;Afonso et al 2014;Leverett & Jolls 2014), our finding may suggest that the competitiveness of larger seeds is partly mediated by rapid germination.…”
Section: Discussionsupporting
confidence: 92%
“…For example, even within the same weed species, emergence varied based on different seed sizes (Tanveer et al, 2013). These authors classified Convolvulus arvensis seeds as large, medium or small.…”
Section: Resultsmentioning
confidence: 99%
“…The soil is an environmental factor that also determines plant growth which is influenced by the organism, climate, topography, time and parent material (Hoveizch 1997). There are many soil factors (variables) that influence the diversity and distribution of plant species, such as organic matter, exchangeable cation, soil types and other soil factors Tanveer et al (2013) suggest that the Celosia arvensis tends to grow better in neutral and slightly acidic soil as compared to alkaline soil environments.…”
Section: Habitat Of Smilax and Its Interaction With Abiotic Factorsmentioning
confidence: 99%